Prarancangan Pabrik Dimetil Eter Dari Tandan Kosong Sawit (TKS) Menggunakan Proses Indirect Synthesis Dengan Disain Alat Utama Destilasi Dimetil Eter - Nurrahmiati Nurrahmiati; Panca Setia Utama (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The level of LPG demand is increasing every year, even the import of LPG has been carried out for a long time, but the need for LPG has not been fulfilled, this has led to the establishment of a Dimethyl Ether (DME) factory to cover LPG needs in Indonesia. DME can also be used as a propellant in aerosol form such as hairspray, insecticide, and air freshener. The main raw material used in the manufacture of DME is Oil Palm Empty Bunches (TKS). This factory is built with a capacity of 50,000 tons / year which will be established in Pelintung, Medang Kampai District, Dumai. The DME production process is carried out by the Indirect Synthesis process where DME is made through 2 processes, namely methanol synthesis from EFB and DME synthesis from methanol. Methanol synthesis and DME synthesis occur in 2 different reactors where methanol is first synthesized then dehydrated to DME. The main equipment design in this plant is the DME Distillation which functions to separate DME as the top product from Methanol and water as the basic product. The feed, distillate and bottom temperatures in this distillation tower are 48,10C, 33,70C and 231.40C with a pressure of 9 atm. , 97 m. Economic analysis on the design of this factory shows that this factory is feasible to be established with a factory Payback Period (PBP) of 2.29 years and a BEP at a capacity of 38%. Keywords: Dimethyl ether, economic Analysis, empty palm fruit bunches